Evaluating territorial management of integrated development region (RIDE-DF) and its effect on land use land cover transformation - Eder Renato Merino; Daniel A. de Azevedo; Mathias Omar T. Alvarez; Allan da Silva Ramalho (Journal of Maps)
In Brazil, the decentralized federative structure of the State, consisting of four autonomous political levels – Union, states, Federal District, and municipalities – alongside its vast territory, necessitates innovative strategies for territorial management. The Integrated Development Region (RIDE) was regulated in 1985, establishing a standardized region composed of municipalities spanning multiple states, prioritizing coordinating federal actions with regional policies. This study aims to assess the impact of Federal District RIDE on land use and land cover changes (LULC) within its territory. As a data source, we utilized MapBiomas collection data for the region. This collection employs multi-temporal (1985–2022) Landsat satellite imagery classifications, ensuring accurate and current information. Additionally, socioeconomic indicators were incorporated to comprehend changes during and post-RIDE-DF implementation. Insights from this study may support decision-making processes concerning land management, urban planning, and conservation endeavors within the region.